MINIMUM WAGE POLICY AND HDI IMPROVEMENT: THE KEY TO REDUCING THE OPEN UNEMPLOYMENT RATE KARANGANYAR REGENCY - Rahmad Wahyu Hidayat (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2025)
Indonesia has a population of approximately 280 million and is one of the largest countries in the world. A large population can lead to problems such as unemployment if not appropriately managed. Based on these conditions, this study aims to analyze the effect of the regency minimum wage and the human development index (HDI) on the open unemployment rate (OUR) in Karanganyar regency. This study employs a quantitative method. Secondary data consists of time series data from the Central Statistics Agency (BPS) from 2017 to 2024. IBM SPSS Statistics Version 26 software was used to analyze the data in this study. The analysis results indicate that the county minimum wage has a significant positive impact on the OUR, meaning that an increase in the minimum wage tends to be followed by a rise in the open unemployment rate. Conversely, the human development index significantly negatively impacts the OUR, indicating that as the HDI increases, the open unemployment rate decreases. The policy implications of this study suggest that local governments should consider strategies to improve human resource quality when determining policies regarding minimum wage increases.